Stolen Manuscript: Lessons Learnt - Sanson, Jacqueline (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
In 2000, the 13th-century Hebrew Bible, known as Hebrew 52, was discovered missing at the National Library of France. Investigations led to the arrest of the National Library of France’s chief curator of Hebrew Collection Michel Garel in 2004. In response to this event the National Library of France has implemented a security plan which includes four main fields: spaces and access controls, preservation and control of collections, measures applied to library staff and readers, and national and international cooperation.